STRATEGI BADAN NARKOTIKA NASIONAL DALAM PENANGGULANGAN NARKOTIKA DI MASA PANDEMI COVID-19 DI INDONESIA - Ernita Dewi; Khalida Ulfa; Safirussalim Safirussalim (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
A survey in Indonesia shows that the range of 2018-2021 from before the COVID-19 pandemic to after the Covid-19 pandemic, narcotics cases increased significantly. The purpose of this study is to analyze the Strategy of the National Narcotics Agency in Preventing Narcotics During the Covid-19 Pandemic in Indonesia. This research uses qualitative and descriptive methods. Sources of data obtained through journals, twitter and websites. The data analysis technique uses Nvivo 12 plus analysis through chart features, twitter sociogram, website. The results showed that the BNN RI strategy in preventing narcotics during the COVID-19 pandemic was through three strategic steps, namely the Soft Power Approach (in the form of prevention activities, community empowerment, rehabilitation and post-rehabilitation so that people have self-defense and deterrence against narcotics abuse), Hard Power Approach (by focusing on strict and measurable law enforcement aspects in dealing with narcotics syndicates) and Smart Power Approach (using information technology in the digital era in efforts to combat narcotics). This strategy is used for sustainable development in the health, economic and social fields of Indonesian society in preventing narcotics crime.